Cellular regeneration and proliferation on polymeric 3D inverse-space substrates and the effect of doxorubicin. Issue 6 (23rd April 2020) - Bobade, Chandrashekhar D.; Nandi, Semonti; Kale, Narendra R.; Banerjee, Shashwat S.; Patil, Yuvraj N.; Khandare, Jayant J.
Abstract : 2D substrates promote cell attachment with lateral compression; 3DIS scaffolding restores the 3D cell structure allowing more realistic cellular-drug responses. Abstract : Spatial arrangement for cells and the opportunity thereof have implications in cell regeneration and cell proliferation. 3D inverse space (3DIS) substrates with micron-sized pores are fabricated under controlled environmental conditions from polymers such as poly(lactic- co -glycolic) acid (PLGA), poly(lactic acid) (PLA) and poly(styrene) (PS). The characterization of 3DIS substrates by optical microscopy, scanning probe microscopy (SPM), etc. shows pores within 1–18 μm diameter and prominent surface roughness extending up to 3.9 nm in height over its base. Conversely, to compare two-dimensional (2D) versus 3DIS substrates, the crucial variables of cell height, cell spreading area and cell volume are compared using lung adenocarcinoma (A549) cells. The results indicate an average cell thickness of ∼6 μm on a glass substrate whereas cells on PLGA 3DIS were ∼12 μm in height, occasionally reaching 20 μm, with a 40% decreased cell spreading area. A549 cells cultured on polymer 3DIS substrates show a cell regeneration growth pattern, dependent on the available spatial volume. Furthermore, PLGA 3DIS cell culture systems with and without graded doxorubicin (DOX) pre-treatment result in potent cell inhibition and cell proliferation, respectively. Additionally, standard DOX administration to A549 cells in the PLGA 3DIS system revealed altered drug sensitivity. 3DIS demonstrates utility in facilitating cellular regeneration and mimicking cell proliferation in defined spatial arrangements.